“EUROPE” AND “THE WEST” IN GEORGIA’S POLITICAL IMAGINATION AND NATIONALIST DISCOURSE - KIRCHANOV, Maxim (CENTRAL ASIA AND THE CAUCASUS, 2010)
The political upheavals of the 2000s caused by the post-authoritarian landslide pushed to fore the problem of nations and nationalism and the question of further development routes.1In 2003, President Shevardnadze lost his post: this marked a turning point in Georgia’s history, which has since been grossly hyperbolized within Georgia’s nationalist discourse. T. Avaliani, for example, has the following to say on this score: “In November 2003, after two civil wars and 12 years of post-Soviet turmoil and suspense, Georgia was the first among the Sovietsuccessor states to tear down the Iron Curtain of the Russian Empire. The Rose Revolution, which liberated the Georgian people from imperial dictatorship and communist legacy, began building a new, civilized, and democratic state.”2Today, the revolution is seen as a key event in Georgia’s current political history. G. Areshidze, a prominent political scientist, commented on the post-revolutionary situation as follows: the new elites inherited a country with a “quasi-balanced constitutional foundation, legislative power … a business community that the state could not control … and several semi-democratic political parties.